Regional Lymphadenitis Related to Bacille Calmette–Guerin Vaccination: A Case Series from a Tertiary Care Childrens’ Hospital - Ekta Narang; Aarshi Gupta; Arti Khatri; Diganta Saikia; Neha Jain; Sonali Tyagi (Indian Pediatrics Case Reports)
Background: Immunization with Bacille Calmette–Guerin (BCG) vaccine, used worldwide for years, for the prevention of tuberculosis, rarely leads to complications like regional lymphadenitis. There is controversy regarding the management of BCG lymphadenitis. We share our experience regarding the management and course of this rare complication in nine infants. Clinical Description: Over a period of 24 months, 9 infants, who had received BCG vaccination after birth, presented to us between 1 and 3 months of age, with left-sided supraclavicular swellings. The infants were otherwise thriving well, with no constitutional symptoms. On examination, the infants were stable with normal systemic examination. Local examination revealed all the swellings to be supraclavicular lymphadenopathies, two of them being suppurative. Thus, the infants fulfilled the clinical criteria for BCG regional lymphadenitis. Management and Outcome: Fine-needle aspiration cytology from the swellings of all infants was consistent with BCG lymphadenitis. Two of the smears were positive for acid-fast bacilli. Besides percutaneous pus aspiration in two infants, no other intervention was done in any of the infants, and no antibiotics nor antitubercular treatment was administered. With observation and regular follow-up, the lymphadenopathies resolved over time in all the infants. Conclusion: This case series creates awareness regarding the benign, self-resolving nature of BCG regional lymphadenitis, which may be followed conservatively without any medical or surgical intervention.